Virulence Factors and Molecular cloning of Outer Membrane Protein (OMP) gene from virulent Aeromonas hyrophila isolated from infected gold fish Carassius auratus (Bangladesh Journal of Microbiology, 2012)
Aeromonas hyrophila strains AHV1, AHV2 and AH3 were isolated and identified from Muscle tissue, intestine, body fluid and gills of infected gold fish Carassius auratus. In order to study their virulence, LD50 tests against  normal gold fish, proteolytic, haemolytic and challenge studies were performed. The virulence studies revealed that, both AHV1 and AHV2 strains are highly positive for proteolytic and haemolytic properties. The LD50 data showed that, the fish C. auratus are highly susceptible to A. hyrophila strains AHV1 and AHV2 at cent percent lethal rate. The survival of C. auratus significantly (P